2018
DOI: 10.18585/inabj.v10i3.441
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Cytotoxic Effects of Cosmos caudatus Ethanolic Extract on Cervical Cancer

Abstract: BACKGROUND: Oxidative stress is closely related to all aspects of cancer. Cosmos caudatus ethanolic extract (CCEE) has been proved to have antioxidant effect that inhibited cancer cell growth due to its bioactive compounds such as catechin, quercetin and chlorogenic acid. This study aimed to evaluate antioxidant and anticancer activity of CCEE and its compounds.METHODS: Total phenol was measured according to the Folin-Ciocalteu method. Catechin, quercetin and chlorogenic acid contained in CCEE were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
13
0
5
Order By: Relevance
“…The difference in CCW activities between the two assays may be caused by the structure difference of the preformed radicals. 20 C. caudatus leaf extracts have been shown to have high antioxidant activities in different studies [21][22][23][24][25] . In one study, the antioxidant capacity of C. caudatus was reported to have the highest potency among 21 tropical plant extracts evaluated, and was comparable in potency to some synthetic antioxidants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in CCW activities between the two assays may be caused by the structure difference of the preformed radicals. 20 C. caudatus leaf extracts have been shown to have high antioxidant activities in different studies [21][22][23][24][25] . In one study, the antioxidant capacity of C. caudatus was reported to have the highest potency among 21 tropical plant extracts evaluated, and was comparable in potency to some synthetic antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that the antioxidant activities associated with this species may be attributed to the flavonoids present, while vitamin C may also contribute to the observed antioxidant effects. 21 Flavonoids of the flavonol and flavone subclasses are widely documented to mediate antioxidant effects. [27][28][29] In this study, high-resolution LC-UV-MS/MS analysis of CCW revealed the detection of compounds assigned as quercetin, kaempferol and apigenin glycosides assigned from their observed [M + H] + ions (Table 3) [27][28][29][30] it may be concluded that their detection in CCW may have contributed considerably to the antioxidant effects observed.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7] [8] Aktivitas biologik lainnya meliputi antidiabetes, antihiperlipidemia dan sitotoksik. [9][10] [11] . Beberapa penelitian juga telah mengungkapkan mengenai keterkaitan kandungan senyawa metabolit sekunder dan aktivitasnya.…”
Section: Pendahuluanunclassified
“…Total phenolic content was asserted as gallic acid equivalence (GAE) in μg/mg sample. This test was done triplicate (Nurhayati et al, 2018;Rusmana et al, 2017;Widowati et al, 2015;Prahastuti et al, 2019b).…”
Section: Phenolic Content Assaymentioning
confidence: 99%